Finanzierungserfordernisse des sächsischen Handwerks: gegenwärtige Situation, Perspektiven und wirtschaftspolitische Implikationen - Joachim Ragnitz; Johannes Steinbrecher (ifo Institut, Niederlassung Dresden, 2011)
Das Handwerk ist mit seinen vielen kleinen und mittleren Betrieben ein Kernstück der deutschen Wirtschaft. Ein wirtschaftlich gesundes Handwerk ist ein wichtiger Wirtschaftsfaktor für die Region. Dazu bedarf es jedoch eines ausreichenden Zugangs zu Finanzierungsinstrumenten. Das Handwerk ist aufgrund seiner Unternehmens- und Branchenstruktur hierbei mit spezifischen Problemen konfrontiert. Die vorliegende Untersuchung liefert Einblicke in die gegenwärtige Finanzierungssituation der Handwerksbetriebe und diskutiert, inwiefern sich diese verbessern lässt. – – The trade firms comprise the most versatile economic sector. With many small and medium sized enterprises this sector is important for the German economy. Prosperintrade firms are also essential for the regional economy in Saxony. These firms require access to adequate financial instruments. Due to its corporate and sector structure the trade faces specific problems. This study therefore provides insights into the current financial situation of trade companies. First, to understand the financing situation of the trade, current literature about the financial situation of small and medium-sized enterprises is discussed with regard to specific implications for the trade. Second, a survey of selected Saxon trade companies analyses the current financing situation. To acquire insights from the investors' perspective, representatives of the regional credit/banking sector are asked to evaluate the current situation. The results of the surveys are examinedusing both qualitative and quantitative methods.
Keywords: G10; L20; L60; 330; Handwerk; Finanzierung; Finanzmanagement; Kapitalbedarf; Sachsen; Handwerk; Finanzierung; Kreditrationierung; Meinung; Handwerkspolitik; Sachsen